Città e climate change. La vulnerabilità delle aree urbane alle isole di calore - Gaglione, Federica (Smart City, Urban Planning for a Sustainable Future, 2022)
Climate change represents one of the main threats to which our planet is called to respond, both in terms of mitigating the phenomena and adapting to the impacts on the built environment. The International Panel for Climate Change (IPCC), in its latest reports, highlights how the phenomena related to climate variability will intensify in the coming decades and extreme climate-related events will pose a growing risk, especially for our cities. In this direction, the research work addressed within this volume aims to contribute to scientific research about the vulnerability of urban areas to heat islands. In detail, the volume is divided into four chapters. The first two illustrate the state of the art, developing a comprehensive cognitive picture of this issue. The different approaches and the different models are highlighted also through the reading of the European and Italian adaptation plans. The strategies, actions and interventions proposed to improve the structure and organization of the territory are examined. The third chapter proposes a methodology aimed at take-over of temperatures with the use of spatial analysis methods in a GIS environment in relation to urban characteristics, useful for measuring the vulnerability of urban systems to heat islands, in accordance with the theories and models issued by the IPCC. Finally, in the fourth chapter, a first experimentation on the city of Naples of the results of the research work is reported, defining the portions of the territory of the V and VIII municipalities where it is necessary to intervene with priority, as a first step in the development of an instrument to support decisions for public administrations.